The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1002/adfm.202210298
|View full text |Cite
|
Sign up to set email alerts
|

Hexagonal Co9S8: Experimental and Mechanistic Study of Enhanced Electrocatalytic Hydrogen Evolution of a New Crystallographic Phase

Abstract: The crystallographic phase is one of the most important parameters in determining the physicochemical properties of an electrocatalyst. However, existing understanding of phase‐performance relationship is still very limited, especially for unconventional phases. Herein, the experimental discovery of the hexagonal close‐packed (hcp) phase of Co9S8 is presented. This is the first demonstration of the hexagonal phase of Co9S8, and through correlated experimental and computational data, the first to elucidate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…In Figure c, it is observed that the signals at 779.23 (Co 2p 3/2 ) and 794.43 eV (Co 2p 1/2 ) originate from Co 3+ , while the peaks at 781.86 (Co 2p 3/2 ) and 798.55 eV (Co 2p 1/2 ) belong to Co 2+ . The S 2p spectra of samples reveal three different chemical species (Figure d), including S 2– (162.17 and 163.20 eV), S n 2– (164.22 and 165.42 eV), and SO x 2– (169.33 eV) . The binding energy of P 2p shifts negative, and the binding energies of Co 2p and S 2p shift positive, indicating a strong interaction between Co 9 S 8 and RP, making the transfer of electrons from Co 9 S 8 to RP.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…In Figure c, it is observed that the signals at 779.23 (Co 2p 3/2 ) and 794.43 eV (Co 2p 1/2 ) originate from Co 3+ , while the peaks at 781.86 (Co 2p 3/2 ) and 798.55 eV (Co 2p 1/2 ) belong to Co 2+ . The S 2p spectra of samples reveal three different chemical species (Figure d), including S 2– (162.17 and 163.20 eV), S n 2– (164.22 and 165.42 eV), and SO x 2– (169.33 eV) . The binding energy of P 2p shifts negative, and the binding energies of Co 2p and S 2p shift positive, indicating a strong interaction between Co 9 S 8 and RP, making the transfer of electrons from Co 9 S 8 to RP.…”
Section: Resultsmentioning
confidence: 94%
“…45 The S 2p spectra of samples reveal three different chemical species (Figure 3d), including S 2− (162.17 and 163.20 eV), S n 2− (164.22 and 165.42 eV), and SO x 2− (169.33 eV). 46 The binding energy of P 2p shifts negative, and the binding energies of Co 2p and S 2p shift positive, indicating a strong interaction between Co 9 S 8 and RP, making the transfer of electrons from Co 9 S 8 to RP. .…”
Section: Structures and Morphology X-ray Diffraction (Xrd)mentioning
confidence: 99%
“…In another study, Pd-doped 1T MoS 2 with sulfur vacancies was successfully prepared via a spontaneous interfacial redox reaction between MoS 2 and Pd­(II), where Pd substitutes the Mo site simultaneously inducing the phase change of MoS 2 from the original 2H to 1T (Figure c). Very recently, Ho et al demonstrated the unconventional hcp Co 9 S 8 and successfully doped Fe into this novel phase structure . Besides the metal dopant, some nonmetallic species have also been adopted as dopants to be incorporated into unconventional nanomaterials, such as B and Se .…”
Section: Structural Configurations Of Multicomponent Metallic Nanomat...mentioning
confidence: 99%
“…Very recently, Ho et al demonstrated the unconventional hcp Co 9 S 8 and successfully doped Fe into this novel phase structure. 180 Besides the metal dopant, some nonmetallic species have also been adopted as dopants to be incorporated into unconventional nanomaterials, such as B 181 and Se. 182 As demonstrated by the structure model in Figure 6d, our group reported boron-incorporated amorphous IrO x (IrO x -B) by a boric acid assisted method.…”
Section: Doped and Surface-modified Nanomaterialsmentioning
confidence: 99%
“…My main research interests are in electronic materials and devices, emphasizing two application areas: sensing as well as energy storage and conversion. My group and I build advanced electronic devices through optimizing a materials structure-property relationship and device architecture, for example, synthesizing new crystallographic phases, 1 studying crystal growth and nucleation, 2 engineering the interlayer space in 2D materials, 3 molecular design, 4 building hierarchical structures across multi length-scales, 5 and creating new device architectures. 6 In our effort, it dawned on us that there is a recurring theme, especially true for sensors and electrocatalysts, which is the idea of balancing order against disorder.…”
mentioning
confidence: 99%